The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/gels7040184
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of Alginate-Gelatin Hydrogels with Bioceramics for Biomedical Applications: A Comparative Study

Abstract: This study states the preparation of novel ink with potential use for bone and cartilage tissue restoration. 3Dprint manufacturing allows customizing prostheses and complex morphologies of any traumatism. The quest for bioinks that increase the restoration rate based on printable polymers is a need. This study is focused on main steps, the synthesis of two bioceramic materials as WO3 and Na2Ti6O13, its integration into a biopolymeric-base matrix of Alginate and Gelatin to support the particles in a complete sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Composite implants were obtained by printing a mixture of alginate-gelatin hydrogels and bioceramics including Al 2 O 3 , TiO 2 , ZrO 2 , etc. by Avila-Ramirez et al These implants are shown in Figure e, the implants with consistent architecture and well-defined boundaries. The implants were immersed in simulated body fluids for 21 days in which the levels of calcium and phosphorus concentrations were measured, and the indicators showed that the composite implant supported the growth of the endothelial cell C166 line.…”
Section: Advances In Additive Manufacturing Of Bioceramic Implantsmentioning
confidence: 83%
See 2 more Smart Citations
“…Composite implants were obtained by printing a mixture of alginate-gelatin hydrogels and bioceramics including Al 2 O 3 , TiO 2 , ZrO 2 , etc. by Avila-Ramirez et al These implants are shown in Figure e, the implants with consistent architecture and well-defined boundaries. The implants were immersed in simulated body fluids for 21 days in which the levels of calcium and phosphorus concentrations were measured, and the indicators showed that the composite implant supported the growth of the endothelial cell C166 line.…”
Section: Advances In Additive Manufacturing Of Bioceramic Implantsmentioning
confidence: 83%
“…As the concentration of HA increased, the morphology of the hydrogel changed from translucent to opaque. 95 Copyright 2021 MDPI. g) GelMA-HA hydrogel on the first day of live−dead analysis; HA can be seen as black needle-like bodies.…”
Section: Additive Manufacturing Of Bioceramic/hydrogelmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, viscosity assumes a critical role in preserving hydrogel stability during the extrusion process, as an increased layering of hydrogel induces augmented pressure. [45] Giuseppe et al have indicated that extending the crosslinking duration also constitutes a vital aspect in augmenting the mechanical properties of hydrogel scaffolds. [33] In our study, the Alg6Gel6 concentration closely approximated the 5% alginate/6% gelatin hydrogel concentration in Giuseppe et al's investigation.…”
Section: Discussionmentioning
confidence: 99%